The impact of techno complexity on work performance through emotional exhaustion - Yasinta, Tiurma; Firdaus, Firdaus; Haqq, Zulkifli Nurul; Run, Pharatt (Universitas Ahmad Dahlan, 2024)
Technology has become an integral part of work life, providing significant benefits for increasing productivity and competitiveness. However, the use of technology also carries risks, especially in the form of technostress, namely, the stress that arises from using technology. This study aimed to investigate the impact of technological complexity as a technostress trigger on work performance among employees in micro, small, and medium enterprises in Semarang, Indonesia, with emotional exhaustion as a potential mediator. The sample for this study consisted of 315 micro, small, and medium-sized enterprise workers in various sectors. Data were collected through surveys and analyzed using structural equation modeling and partial least squares. The research results show that technological complexity negatively affects emotional exhaustion, but does not significantly affect work performance. By contrast, emotional exhaustion negatively influenced work performance. However, there is insufficient evidence to support the mediation of emotional exhaustion between technological complexity and workplace performance. These findings emphasize the importance of considering additional factors beyond techno complexity in shaping work performance as well as the importance of organizational support in mitigating the negative impact of techno complexity on employee well-being and performance in micro, small, and medium-sized enterprises.